Performance Comparison of Signal Timing Optimization and Underpass at Ahmad Yani Signalized Intersection - Miftakul Ma’arif; Kurnia Hadi Putra; Ratih Sekartadji; Theresia Maria C.A. (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Traffic congestion at signalized intersections has become a major challenge in urban transportation, particularly at intersections affected by heavy traffic demand and railway crossing operations. This study evaluates the operational performance of the Ahmad Yani–Margorejo Indah signalized intersection in Surabaya and compares the effectiveness of two traffic engineering alternatives: signal timing optimization and underpass construction. The analysis was conducted using the 2023 Indonesian Highway Capacity Guidelines (PKJI 2023) based on intersection geometry, peak-hour traffic volume, vehicle composition, roadside friction, signal timing, and railway crossing characteristics. The existing condition indicated oversaturated traffic flow with a maximum degree of saturation of 1.56 during the evening peak hour, resulting in excessive delays, long vehicle queues, and Level of Service (LOS) F. Signal timing optimization improved traffic performance by redistributing effective green times among signal phases; however, several approaches remained oversaturated. In contrast, the underpass alternative significantly reduced traffic conflicts, increased roadway capacity, lowered the degree of saturation, and virtually eliminated intersection delays. The findings demonstrate that underpass development provides the most effective long-term solution for improving intersection performance under high traffic demand. This study contributes practical insights for selecting appropriate traffic engineering strategies for complex urban signalized intersections.